Demand Shocks as Technology Shocks - Bai, Yan; Ríos-Rull, José-Víctor; Storesletten, Kjetil (Review of Economic Studies, 2026)
We provide a macroeconomic theory where demand for goods has a productive role. A search friction prevents perfect matching between producers and potential customers. Larger demand induces more search, which, in turn, increases GDP and measured total factor productivity (TFP). We embed the product-market friction in a standard neoclassical model and estimate it using Bayesian techniques. Business cycles are driven by preference shocks, true technology shocks, and investment-specific shocks. Preference shocks have qualitatively similar effects as true productivity shocks. These shocks account for a large share of the fluctuations in consumption, GDP, and measured TFP and can be identified using shopping time data.